Knowledge Ottoman Turkish Medicine : From Methods of Immunization Traditional to Pioneer World Vaccine - Rafid Sugandi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
This research explores the history of immunization